Photocatalytic-electrocatalytic dual hydrogen production system - Aydemir, Mehmet; Akyuz, Duygu; Agopcan, Burag; Sener, M. Kamm; Albayrak, Fatma Karaca; Sarzoglu, Ceuat; Koca, Atif (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In this paper, in order to produce efficient and low cost hydrogen by using alternative energies with simple ways; a photocatalytic electrocatalytic dual hydrogen production system (PEHPS) which combined discontinuous photocatalytic and electrocatalytic systems in one continuous dual system was designed and optimized. In the photocatalytic chamber of PEHPS, nano-sized Cd(1-x)ZnxS/Pt photocatalysts were utilized. The synthesized Cd(1-x)ZnxS/Pt photocatalysts were characterized with scanning electron microscopy (SEM), X-Ray Diffraction (XRD) and diffuse reflectance UV Vis spectroscopy. The most active photocatalyst having CdZnS2 core and 10% Pt shell showed 24.0 mLg(-1) h(-1) (963.6 gmol g 1 h(-1)) hydrogen evolution rate with 4.01% solar energy conversion efficiency (SECE%). S2O3-2 produced in the photocatalytic chamber of PEHPS was used as redox species in the electrocatalytic chamber. This process decreased the cell potential of water electrolysis from 2.50 V to 1.70 V on glassy carbon electrodes. Moreover, usage of electro-polymerized metallophthalocyanines (Poly-MPc) as cathode active electrocatalyst, the over-potential of cathode of the electrocatalytic chamber for hydrogen reduction reaction decreased by 0.230 V. (C) 2015 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen evolution reaction; Electrocatalyst; Photocatalyst; Phthalocyanine; CdZnS; Core-shell structure; BULK COMPOSITE PHOTOCATALYSTS; SOLID-SOLUTION PHOTOCATALYSTS; HIGH QUANTUM EFFICIENCY; H-2 EVOLUTION; OXYGEN EVOLUTION; SOLAR-ENERGY; PT-PDS/CDS; WATER; CDS; OXIDATION; Chemistry; Electrochemistry; Energy & Fuels